Getting out of mitosis: spatial and temporal control of mitotic exit and cytokinesis by PP1 and PP2A - Holder, James; Poser, Elena; Barr, Francis A. (FEBS letters, 2019)
Here, we will review the evidence showing that mitotic exit is initiated by regulated proteolysis and then driven by the PPP family of phosphoserine/threonine phosphatases. Rapid APC/CCDC20 and ubiquitin‐dependent proteolysis of cyclin B and securin initiates sister chromatid separation, the first step of mitotic exit. Because proteolysis of Aurora and Polo family kinases dependent on APC/CCDH1 is relatively slow, this creates a new regulatory state, anaphase, different to G2 and M‐phase. We will discuss how the CDK1‐counteracting phosphatases PP1 and PP2A‐B55, together with Aurora and Polo kinases, contribute to the temporal regulation and order of events in the different stages of mitotic exit from anaphase to cytokinesis. For PP2A‐B55, these timing properties are created by the ENSA‐dependent inhibitory pathway and differential recognition of phosphoserine and phosphothreonine. Finally, we will discuss how Aurora B and PP2A‐B56 are needed for the spatial regulation of anaphase spindle formation and how APC/C‐dependent destruction of PLK1 acts as a timer for abscission, the final event of cytokinesis.